Non-functioning pituitary adenomas: indications for pituitary surgery and post-surgical management - Esposito, Daniela; Olsson, Daniel S.; Ragnarsson, Oskar; Buchfelder, Michael; Skoglund, Thomas; Johannsson, Gudmundur (Pituitary, 2019)
Purpose: Non-functioning pituitary adenomas (NFPAs) are associated with impaired well-being, increased comorbidities, and reduced long-term survival. Data on optimal management of NFPAs around surgical treatment are scarce, and postoperative treatment and follow-up strategies have not been evaluated in prospective trials. Here, we review the preoperative, perioperative, and early postoperative management of patients with NFPAs. Methods: We searched Medline and the Cochrane Library for articles published in English with the following items “Pituitary neoplasms AND Surgery” and “Surgery AND Hypopituitarism”. Studies containing detailed analyses of the management of NFPAs in adult patients, including pituitary surgery, endocrine care, imaging, ophthalmologic assessment and long-term outcome were reviewed. Results: Treatment options for NFPAs include active surveillance, surgical resection, and radiotherapy. Pituitary surgery is currently recommended as first-line treatment in patients with visual impairment due to adenomas compressing the optic nerves or chiasma. Radiotherapy is reserved for large tumor remnants or tumor recurrence following one or more surgical attempts. There is no consensus of optimal pre-, peri-, and postoperative management such as timing, frequency, and duration of endocrine, radiologic, and ophthalmologic assessments as well as management of smaller tumor remnants or tumor recurrence. Conclusions: In clinical practice, there is a great variation in the treatment and follow-up of patients with NFPAs. We have, based on available data, suggested an optimal management strategy for patients with NFPAs in relation to pituitary surgery. Prospective trials oriented at drawing up strategies for the management of NFPAs are needed.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Endocrine care; Hypopituitarism; Pituitary adenomas; Pituitary surgery; Surgical outcome